2018
DOI: 10.1002/chem.201803418
|View full text |Cite
|
Sign up to set email alerts
|

Polycrystalline and Single‐Crystal Cu Electrodes: Influence of Experimental Conditions on the Electrochemical Properties in Alkaline Media

Abstract: Single and polycrystalline Cu electrodes serve as model systems for the study of the electroreduction of CO , CO and nitrate, or for corrosion studies; even so, there are very few reports combining electrochemical measurements with structural characterization. Herein both the electrochemical properties of polycrystalline Cu and single crystal Cu(1 0 0) electrodes in alkaline solutions (0.1 m KOH and 0.1 m NaOH) are investigated. It is demonstrated that the pre-treatment of the electrodes plays a crucial role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 103 publications
(102 reference statements)
2
71
0
Order By: Relevance
“…This is similar to the experiments by Schouten et al . We must note that CVs reported in the literature on Cu single‐crystalline electrodes depend strongly on both the surface pre‐treatment and the selected potential range . Recently, Engstfeld et al.…”
Section: Methodology and Resultsmentioning
confidence: 97%
“…This is similar to the experiments by Schouten et al . We must note that CVs reported in the literature on Cu single‐crystalline electrodes depend strongly on both the surface pre‐treatment and the selected potential range . Recently, Engstfeld et al.…”
Section: Methodology and Resultsmentioning
confidence: 97%
“…subjected a Cu(100) surface to successive cycles of Ar + sputtering and annealing under ultra‐high vacuum condition and at 1000 K, followed by direct transfer to the electrochemical cell, without exposure to the electrochemical cell. This protocol ensured high surface ordering as demonstrated by ex‐situ STM measurements, with terraces >50 nm in width (in comparison, an STM images suggest that other treatments, involving air‐transfer and without a thermal annealing step, yield much rougher surfaces) . They demonstrated that the slight discrepancy between the reported blank voltammograms in literature, particularly for Cu(100), was related to the presence of defects that are likely to be induced by conventional surface pre‐treatments involving electropolishing and exposure of the electrode in air (Figure D).…”
Section: Structure Sensitivity In Co2 Reductionmentioning
confidence: 81%
“…Different surface pre‐treatments can be applied to Cu(hkl) in order to ensure surface ordering under experimental conditions. These pre‐treatments usually consist of both mechanical and electrochemical polishing of the surface (Figure C) and transferring through air . However, there is still slight discrepancy between the different voltammetric profiles reported in literature for Cu(hkl).…”
Section: Structure Sensitivity In Co2 Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cu(111) was chosen as a sample due to Cu being the only pure metal electrocatalyst which can catalyse the reduction of CO 2 to a range of different interesting products with a reasonable faradaic efficiency . Furthermore, the fundamental EC properties of Cu are still under debate . The electrolytes were picked as they are prevalent in the literature for these sample types.…”
Section: Introductionmentioning
confidence: 99%